An International Urogynecological Association (IUGA)/International Continence Society (ICS) joint report on the terminology for female anorectal dysfunction. (January 2017) - Sultan, Abdul; Monga, Ash; Lee, Joseph; Emmanuel, Anton; Norton, Christine; Santoro, Giulio; Hull, Tracy; Berghmans, Bary; Brody, Stuart; Haylen, Bernard
Abstract Introduction and hypothesis The terminology for anorectal dysfunction in women has long been in need of a specific clinically-based Consensus Report. Methods This Report combines the input of members of the Standardization and Terminology Committees of two International Organizations, the International Urogynecological Association (IUGA) and the International Continence Society (ICS), assisted on Committee by experts in their fields to form a Joint IUGA/ICS Working Group on Female Anorectal Terminology. Appropriate core clinical categories and sub classifications were developed to give an alphanumeric coding to each definition. An extensive process of twenty rounds of internal and external review was developed to exhaustively examine each definition, with decision-making by collective opinion (consensus). Results A Terminology Report for anorectal dysfunction, encompassing over 130 separate definitions, has been developed. It is clinically based with the most common diagnoses defined. Clarity and user-friendliness have been key aims to make it interpretable by practitioners and trainees in all the different specialty groups involved in female pelvic floor dysfunction. Female-specific anorectal investigations and imaging (ultrasound, radiology and MRI) has been included whilst appropriate figures have been included to supplement and help clarify the text. Interval review (5–10 years) is anticipated to keep the document updated and as widely acceptable as possible. Conclusions A consensus-based Terminology Report for female anorectal dysfunction terminology has been produced aimed at being a significant aid to clinical practice and a stimulus for research.